2014 International Conference on Management Science &Amp; Engineering 21th Annual Conference Proceedings 2014
DOI: 10.1109/icmse.2014.6930437
|View full text |Cite
|
Sign up to set email alerts
|

Linkage between patent management and technological innovation performance: New evidence from Chinese high-tech enterprises

Abstract: Given the changing role of patents within enterprises, this study aims to investigate the linkage between patent management (PM) and technological innovation performance (TIP) from a resource-based perspective. According to 252 valid samples collected from 106 high-tech enterprises, the analysis results show that patent acquisition (PA) has positively effect on patent protection (PP) and patent commercialization (PC); PP has positively effect on PC and PA; PA and PC have positively effect on TIP. Therefore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…The study of described the reliable basis for identifying the real innovation signals of enterprises in the case of government subsidies [14]. Cao and Su(2012) took typical Chinese high-tech industries from 1995 to 2008 as samples and concluded that both R&D input and non-R&D input can improve innovation performance, but high output may not be achieved due to industrial differences [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study of described the reliable basis for identifying the real innovation signals of enterprises in the case of government subsidies [14]. Cao and Su(2012) took typical Chinese high-tech industries from 1995 to 2008 as samples and concluded that both R&D input and non-R&D input can improve innovation performance, but high output may not be achieved due to industrial differences [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because the diversified innovation activities of enterprises are not easy to measure uniformly, it is still difficult for the academic community to reach a unified conclusion on the measurement of technological innovation performance. Nevertheless, they all agree on the important role of enterprise patents in the study of technological innovation performance [50]. At present, the number of patent applications is also widely used as a proxy variable for technological innovation performance in research [28].…”
Section: Technical Innovation Performancementioning
confidence: 99%
“…The process of commercialization is to choose the right time to make the company get the investment opportunity or the highest profit [6]. Cao Yong believes that the process of patent commercialization mainly includes alternative patents into products within the validity period and recovering research and development costs and obtaining benefits through licensing and transforming [7]. Technological innovation is a kind of economic activity, which usually needs to go through the stages of invention, creation, technology transformation, commercial production and product sales [8].…”
Section: Connotation Of Patent Commercializationmentioning
confidence: 99%